PENERAPAN METODE VIRTUAL ROUTER REDUNDANCY PROTOCOL (VRRP) PADA YAYASAN MASJID AL IKHLAS - Usanto Usanto; Lela Nurlaela; Purwono Purwono (Institut Teknologi dan Bisnis Swadharma, 2022)
The computer network is a very important aspect of our life today. Without a computer network, we cannot communicate with one another if separated by distance and time. Therefore, the availability of computer networks today is very important to support communication and even to support our work 24 hours a day. In line with these developments, there are still many network problems, especially at the Al Ikhlas Mosque Foundation, one of these factors is the lack of maintenance in terms of hardware that is not supported with the appropriate specifications. Based on the problems encountered and the results of the analysis using the SWOT method, it was concluded that there is a need to optimize the development of network technology at Masjid Al Ikhlas Foundation as an innovation in security issues and network smoothness by applying the VRRP (Virtual Router Redundancy Protocol) method. To support the VRRP method, it is necessary to conduct training for employees of the Masjid Al Ikhlas Foundation in the field of IT technology to deal with increasingly rapid technological developments, and it is also necessary to perform routine maintenance on network devices